Character Education Through Traditional Ranup Lam Puan Dance: A Study of Kindergarten Teachers at Almuna Bireuen - Rudy Juli Saputra; Novysa Basri; Vinny Aryesha (Catharsis, 2024)
The purpose of this study was to determine character education through the learning process of traditional Ranup Lam Puan dance for teachers of Almuna Bireuen Kindergarten, namely implementing the values ​​of character education contained in the traditional Ranup Lam Puan dance. The type of research used in this study is qualitative interpretative. The researcher in this case describes the reality accurately and factually about the problems raised in the study, namely regarding the implementation of character education through the learning process of Traditional Ranup Lam Puan Dance for teachers at Almuna Bireuen Kindergarten. Data collection in this study consisted of observation, interviews, and document studies. The data analysis technique used interactive model data analysis consisting of data reduction, data presentation, and data verification. The results of the study showed that Almuna Bireuen Kindergarten teachers had implemented character education through traditional Ranup Lam Puan dance well in classroom learning with their students. The form of school or class activities and programs ran well and regularly according to the implementation schedule. So that the Ranup Lam Puan Dance has an impact on the learning process by providing character education to children from the Ranup Lam Puan Dance Movement which can be seen from the behavior of children who respect guests who come to school.